Effect on haemostasis of different replacement fluids during therapeutic plasma exchange—A comparative multicentre observational study. Issue 6 (24th August 2022) - Kohli, Ruchika; Allen, Elisa; Platton, Sean; Griffin, James; Manson, Lynn; MacCallum, Peter; Green, Laura
Abstract: Introduction: Therapeutic plasma exchange (TPE) is used for several chronic conditions with little evidence on the efficacy and safety of different choice of replacement fluid. Measurement of haemostasis, particularly in vitro thrombin generation, could play a role in determining the immediate efficacy of different fluid replacement. Aim: To determine the impact of different TPE replacement fluid regimens on haemostatic assays. Methods: Prospective observational multi‐centre cohort study in adult patients 18 years and older evaluating haemostatic changes between four different TPE regimens: (1) 5% human albumin solution (Alb) only, (2) 50:50 mix of 5% Alb + modified gelatin, (3) 70:30 mix of 5% Alb and normal saline (NS), and (4) solvent‐detergent, virus‐inactivated fresh frozen plasma (FFP) (either alone or combined with other fluids). Twenty‐one haemostasis variables were analysed (procoagulant, anticoagulant and fibrinolytic factors) pre and post TPE sessions, including in vitro thrombin generation. Linear mixed modelling and canonical discriminant analyses were used to examine the effect of TPE fluid type on haemostatic variables. Results: A total of 31 patients with up to 5 TPE sessions each (131 sessions in total) were enrolled. Out of 21 markers analysed using linear mixed modelling, the main effects of fluid type were found to be significant for 19 markers ( P < 0.05), excluding plasminogen activator inhibitor‐1 antigen and thrombin‐anti‐thrombin. Multivariate Analysis of Variance showed significant differences between the fluid types (Wilks' lambda = 0.07; F 63, 245.61 = 5.50; P < 0.0001) and this was supported by a canonical discriminant analysis, which identified the 4 most discriminating markers for fluid types as thrombin generation (lag‐time, time‐to Peak), fibrinogen and Factor V. In our analyses, the effect of FFP on haemostasis was significantly greater compared with other fluid types. Of the non‐FFP fluids, 5% Alb + NS had a lower effect on haemostasis compared to other fluid types (Alb and modified gelatin + 5% Alb). Conclusion: Thrombin generation and fibrinogen discriminated better the effect of different TPE fluids on haemostasis and should be considered as potential markers to evaluate the immediate haemostatic effect of TPE procedures. The use of NS as a TPE replacement fluid had a distinctive impact on thrombin generation and fibrinogen responses compared to other non‐FFP fluids.